4.3k views
0 votes
Given the following formula, solve for a.

Given the following formula, solve for a.-example-1
User IMX
by
5.1k points

1 Answer

2 votes

Answer:

A. a = 2s - b -c

Explanation:

Rearrange the equation in a way that you have only a on one side. When solving equations you can add, subtract, multiply or divide by the same number/variable/expression on the both sides.


s = (a + b + c)/(2)

Multiply by 2 to get rid of the fraction.


s \cdot 2 = (a + b + c)/(2) \cdot 2

On the right side the 2 cancels out:


s \cdot 2 = a + b + c

On the right side next to a are still b and c. But we want a alone. Subtract b.


s \cdot 2 - b = a + b + c - b

b - b on right side gives 0.


s \cdot 2 - b = a + c + 0

The step above is usually skipped, because number + 0 = number.


s \cdot 2 - b = a + c

Next to a there is still c. Subtract c.


s \cdot 2 - b - c = a + c - c

c - c on the left is 0.


s \cdot 2 - b - c = a

So our answer is:


s \cdot 2 - b - c = a

It can be rewritten to (change sides):


a = s \cdot 2 - b - c

And s ยท 2 can be rewritten to 2s:


a = 2s - b - c

User Sparkler
by
6.3k points